Approval of rate for punch through concrete slab for the condensate drain pipe for each HAHU of the classroom - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for approval of rate for punch through concrete slab for the condensate drain pipe for each HAHU of the class room of Brac University new campus project.